PECULIARITIES OF THE OBLIGATION DARE UNDER BULGARIAN LEGISLATION AND IN COMPARATIVE ASPECT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
This scientific paper discusses the features of one of the most common legal obligations – the transfer of property (dare). It is regulated in all legislations throughout the world.The subject of research envelops its peculiarities, according to the two major continental families – the Roman and the German, compared with those of the Anglo-Saxon legal system. Some distinctions of the obligation to transfer property under Bulgarian law, which manifest deviations from its reception via French through Italian law, have been thoroughly reviewed.